Development of applications for vowel migration / modification in sung Filipino (Tagalog) texts and perceived intelligibility - Bustos, Virginia B.; Dela Cruz, Triah Joyce G. (2009)
With the emergence of research on real-time visual feedback to supplement vocal pedagogy, the utilization of technology in the world of music is now seen to accelerate skills learning and enhance cognitive development. The researchers of this project aim to further analyze vowel intelligibility and develop software applications intended to be used not only by professional singers but also by individuals who wish to improve their singing ability. Data in the form of sung vowels and song pieces were obtained from 46 singers who can perform vowel migration. A Listening Test was then conducted on these samples to obtain the ground truth for vowel classification based on human perception. Simulation of human auditory perception of sung Filipino vowels was performed using formant frequencies and Mel-frequency cepstral coefficients as feature vector inputs to a two-stage Discriminant Analysis classifier. The setup resulted to an over-all Training Set accuracy of 89.42% and an over-all Test Set accuracy of 90.88%. Perception accuracy of the classifier, based on the correspondence of vowel classifications obtained from the classifier with the results of the Listening Test, reached 92.23%. Using information obtained from the classifier, offline and online/real-time software applications were developed. The main application features include display of the spectral envelope and spectrogram, pitch and vibrato analysis and direct feedback on the classification of the sung vowel. These features were recommended by surveyed singers and were incorporated in the applications to aid singers to properly adjust formant locations. directly determine the listener's perception of the sung vowel, perform modeling effectively and carry out vowel migration correctly.
Thesis (B.S. Electronics and Communications Engineering) - University of the Philippines, Diliman
Keywords: Speech processing systems; Signal processing -- Digital techniques; Singing; Voice